PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP PEMBELIAN ONLINE MELALUI APLIKASI TOKOPEDIA PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Fajihan, Nurul; Kasim, M. Najib; Sulaiman, Syarifuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of service quality and trust on online purchasing decisions through the Tokopedia application among students of Universitas Muhammadiyah Makassar. This research employed a quantitative approach with a sample of 103 respondents obtained through questionnaire distribution using a Likert scale. The data analysis method used was multiple linear regression with the assistance of SPSS, including validity, reliability, and classical assumption tests. The results indicate that service quality has a positive and significant effect on purchasing decisions with a significance value of 0.049 < 0.05. Trust has a positive but insignificant influence on purchasing decisions with a significance value of 0.067 > 0.05. Simultaneously, service quality and trust influence online purchases with a significance value of 0.000 < 0.05 in the F test. Thus, service quality is a significant determinant factor, while trust has a positive but not yet significant influence on online purchasing decisions of students at Universitas Muhammadiyah Makassar.